Patterns of Tumor Contrast Enhancement Predict the Prognosis of Anaplastic Gliomas with IDH1 Mutation - Wang, Y.Y.; Wang, K.; Li, S.W.; Wang, J.F.; Ma, J.; Jiang, T.; Dai, J.P. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: It is proposed that isocitrate dehydrogenase 1 (IDH1) mutation predicts the outcome in patients with high-grade glioma. In addition, contrast enhancement on preoperative MR imaging reflects tumor biologic features. Patients with anaplastic glioma with the IDH1 mutation were evaluated by using MR imaging to determine whether tumor enhancement is a prognostic factor and can be used to predict survival.MATERIALS AND METHODS: A cohort of 216 patients with histologically confirmed anaplastic glioma was reviewed retrospectively. Tumor contrast-enhancement patterns were classified on the basis of preoperative T1 contrast MR images. Tumor IDH1 status was examined by using RNA sequencing. We used univariate analysis and the multivariate Cox model to evaluate the prognostic value of the IDH1 mutation and tumor contrast-enhancement pattern for progression-free survival and overall survival.RESULTS: In all 216 patients, IDH1 mutation was associated with longer progression-free survival (P = .004, hazard ratio = 0.439) and overall survival (P = .002, hazard ratio = 0.406). For patients with IDH1 mutant anaplastic glioma, the absence of contrast enhancement was associated with longer progression-free survival (P = .038, hazard ratio = 0.473) and overall survival (P = .043, hazard ratio = 0.436). Furthermore, we were able to stratify the progression-free survival and overall survival of patients with IDH1 mutation by using the tumor contrast-enhancement patterns (P = .022 and 0.029, respectively; log-rank).CONCLUSIONS: Tumor enhancement on postcontrast MR imaging is a valuable prognostic factor for patients with anaplastic glioma and IDH1 mutation. Furthermore, the contrast-enhancement patterns could potentially be used to stratify the survival outcome of such patients.AGanaplastic gliomaGTRgross total resection<GTRresidual tumorHRhazard ratioIDH1isocitrate dehydrogenase 1KPSKarnofsky Performance Status ScalePFSprogression-free survivalOSoverall survival